An Appraisal Of Institutional Framework For The Protection Of Internally Displaced Persons In Nigeria Ibijoke P. (2015)
There has been an alarming rise in the number of Internally Displaced Persons (IDPs) in Nigeria in recent times. Internal displacement of Persons in Nigeria is a recurring and large-scale phenomenon that has affected most of the states in Nigeria. The guiding principles on internally displaced persons developed by the United Nations Commission on Human Rights are the first international standards specifically tailored to the needs of IDPs. The guiding principles are consistent with international human rights law and international humanitarian law and to a large extent codify and make explicit guarantees to protect IDPs. The United Nations (UN) Guiding Principles on Internal Displacement of Persons define IDPs as persons or groups of persons who have been forced or obliged to flee or to leave their homes or places of habitual residence in particular as a result of or in order to avoid the effects of armed conflict, situations of generalised violence, violations of human rights or natural or human- made disasters, and who have not crossed an internationally recognised state border.This article generally discusses IDPs in Nigeria and identifies problems encountered by internally displaced persons that are typically caused by shortcomings in the legal and institutional framework on internal displacement in Nigeria and make recommendations on the way forward to alleviate the plight of the IDPs.